2002
DOI: 10.1136/gut.51.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Histological features and HLA class II alleles in hepatitis C virus chronically infected patients with persistently normal alanine aminotransferase levels

Abstract: Objective: A significant proportion of individuals with chronic hepatitis C virus (HCV) infection have persistently normal alanine aminotransferase (ALT) levels. Although data are controversial, such patients usually have weaker histological damage and a lower progression rate of fibrosis. The aims of this study were: (1) to compare demographic, virological, and histological parameters of HCV patients with normal ALT values with those of HCV patients with elevated ALT levels; and (2) to determine whether HLA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 40 publications
6
51
1
Order By: Relevance
“…The host immune response might play an important role in such different outcomes. Many studies assessed an association between HLA Class II and severity of liver injury or favourable outcomes of chronic HCV infection [37][38][39][40]. On the other hand, studies about Class I association with HCV disease patterns is relatively poor.…”
Section: Discussionmentioning
confidence: 99%
“…The host immune response might play an important role in such different outcomes. Many studies assessed an association between HLA Class II and severity of liver injury or favourable outcomes of chronic HCV infection [37][38][39][40]. On the other hand, studies about Class I association with HCV disease patterns is relatively poor.…”
Section: Discussionmentioning
confidence: 99%
“…On the ot her hand, nu me ro us stu di es con duc ted showed that its ac cu racy was higly va ri ab le. 3,4,[7][8][9][10][11][12][13][14][15][16][17][18] In our study, the only sig ni fi cant cor re la ti on was found bet we en se rum AST le vels and HAI in he pa ti tis C. On the ot her hand, in he pa ti tis B, serum AST le vels sho wed cor re la ti on both with fibro sis and HAI. Furt her mo re, a po si ti ve cor re la ti on was al so se en bet we en se rum ALT le vels and HAI in he pa ti tis B ca ses.…”
Section: Discussionmentioning
confidence: 62%
“…A sta tis ti cally sig ni fi - cant cor re la ti on was fo und bet we en bi oc he mi cal tests and his to lo gi cal fin dings in so me of the se studi es, tho ugh not in ot hers. [7][8][9][10][11][12][13][14][15][16][17][18] ALT is con si de red as a li ver-spe ci fic enz yme and nor mally fo und lar gely only in the li ver. Eleva ti ons in se rum ALT le vels are as so ci a ted with rever sib le or ir re ver sib le da ma ge to the he pa tocy te plas ma mem bra ne.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, severity of fibrosis has significant correlation with severity of inflammation, level of AST and presence of steatosis. Above factors have already been validated in literature 4,5,11,18 . We also found that age, weight, sex, AST/ALT ratio and genotype has no impact on fibrosis, where increasing age (> 35 years) and AST / ALT ratio > 1 has correlation with severity of fibrosis (21).…”
Section: Discussionmentioning
confidence: 99%